Responsible Prescribing of Opioids for Chronic Non-Cancer Pain: A Scoping Review - Eleanor Black; Kok Eng Khor; Apo Demirkol (Pharmacy, 2020)
Chronic non-cancer pain is common and long-term opioid therapy is frequently used in its management. While opioids can be effective, they are also associated with significant harm and misuse, and clinicians must weigh any expected benefits with potential risks when making decisions around prescribing. This review aimed to summarise controlled trials and systematic reviews that evaluate patient-related, provider-related, and system-related factors supporting responsible opioid prescribing for chronic non-cancer pain. A scoping review methodology was employed, and six databases were searched. Thirteen systematic reviews and nine controlled trials were included for analysis, and clinical guidelines were reviewed to supplement gaps in the literature. The majority of included studies evaluated provider-related factors, including prescribing behaviours and monitoring for misuse. A smaller number of studies evaluated system-level factors such as regulatory measures and models of healthcare delivery. Studies and guidelines emphasise the importance of careful patient selection for opioid therapy, development of a treatment plan, and cautious initiation and dose escalation. Lower doses are associated with reduced risk of harm and can be efficacious, particularly when used in the context of a multimodal interdisciplinary pain management program. Further research is needed around many elements of responsible prescribing, including instruments to monitor for misuse, and the role of policies and programs.